Asset management of offshore oil and gas installations - Dsouza, Serena Karen (2018)
The UK sector of the North Sea is a mature oil and gas basin subjected to some of the harshest offshore environments with a majority of the oil and gas installations approaching or having exceeded their original design life, often specified as 25 years. It is likely that the operation of these installations will continue for a substantial period in the foreseeable future. However, the ageing nature of these installations present significant challenges to the delivery of high standards of health and safety required by the UK Health and Safety Executive. The issue of ageing installations has been shown to be an important factor in offshore incidents and accidents, leading to an increased risk of accidental loss of hydrocarbon and failures due to equipment deterioration. Two major hazards resulting from ignition of accidental hydrocarbon release are fires and explosions. Failure to minimise the effects of fires and explosions can bring about significant damage to the structural integrity of offshore installations and pose a risk to personnel safety as evidenced by the 1988 Piper Alpha Disaster and the 2010 Deepwater Horizon Explosion and Oil Spill.